Synovial Sarcoma: a Clinicopathological Study with Emphasis on Rare Sites - Ahmed, Imtiaz; Shelly, Divya; Balraam, K V Vinu; Agarwal, Kriti; Bharadwaj, Reena (Annals of Pathology and Laboratory Medicine, 2018)
Background: Synovial sarcoma is an infrequently diagnosed soft tissue sarcoma of the younger population with a male preponderance. Although the disease tends to home itself in the extremities particularly around the joints in the vast majority of cases, it can also occur in other surprising locations which warrant careful and meticulous histopathological examination accompanied by a judicious use of the immunohistochemical panel. Methods: Search of the pathology database was done to identify cases of synovial sarcomas in rare sites. Result: seven cases of synovial sarcoma were identified, three of which were at extremely uncommon sites rendering the diagnosis challenging and intriguing. Conclusion: Differential diagnosis of synovial sarcoma should always be kept in mind in a young patient with a mass lesion of short duration, not only at the extremities but also involving other rarer locations like the lungs, heart and kidney.